Positive electrode active material having a core-shell structure, its manufacturing method, positive electrode plate, secondary battery, battery module, battery pack, and power consumption device

By doping elements and coating three-layer structure in the core of lithium calcium phosphate positive electrode active substance, the problems of reverse position defects and manganese discharge during charging and discharge of traditional positive electrode active substances are solved, and the overall performance of the battery is improved.

JP7651064B2Active Publication Date: 2025-03-25CONTEMPORARY AMPEREX TECHNOLOGY (HONG KONG) LIMITED
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024508714
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-06-20
Publication Date
2025-03-25
Estimated Expiration
2042-06-20

AI Technical Summary

Technical Problem

Traditional lithium calcium phosphate positive electrode active substances are prone to Li/Mn inverse defects during charging and discharging, and are accompanied by the discharge of manganese, resulting in a decrease in battery capacity and deterioration of safety performance and circulation performance.

Method used

The positive electrode active material with a core-shell structure is used to reduce inverse defects and manganese discharge by doping elements A, B, C, and D into the core of LiMnPO4 and coating the three-layer structure on the surface, including crystalline diphosphate, oxide and carbon layers.

Benefits of technology

It significantly reduces the occurrence of Li/Mn inverse defects and manganese discharge, and improves the battery capacity, circulation performance, high-temperature storage performance and safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007651064000073
    Figure 0007651064000073
  • Figure 0007651064000074
    Figure 0007651064000074
  • Figure 0007651064000075
    Figure 0007651064000075
Patent Text Reader

Abstract

The present application provides a positive electrode active material, a method for producing the same, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consumption device, and the positive electrode active material is Li m A x Mn 1-y B y P 1-z C z O 4-n D n and a crystalline Li pyrophosphate coating the core. a MP2O7 and / or M b (P2O7) c A first coating layer containing an oxide M' that coats the first coating layer d O e and a third coating layer containing carbon coating the second coating layer. The positive electrode active material of the present application can reduce the generation of Li / Mn antisite defects, reduce the elution of manganese, and reduce the lattice change rate, thereby improving the capacity of the secondary battery and improving the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application relates to the technical field of secondary batteries, in particular to a positive electrode active material having a core-shell structure, a method for producing the positive electrode active material, a positive electrode plate, a secondary battery, a battery module, a battery pack and a power consuming device. [Background technology]

[0002] In recent years, as the application scope of secondary batteries becomes wider and wider, secondary batteries are widely used in energy storage power systems such as hydroelectric, thermal, wind and solar power stations, as well as in multiple fields such as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, and aerospace. As secondary batteries have made great strides in development, their energy density, cycle performance and safety performance are also required to be higher. As a conventional positive electrode active material of secondary batteries, lithium manganese phosphate is prone to Li / Mn antisite defects during charging and discharging, and manganese leaching is relatively serious, which affects the gram capacity of secondary batteries and causes the safety performance and cycle performance of secondary batteries to be poor. Summary of the Invention [Problem to be solved by the invention]

[0003] The present application has been made in view of the above-mentioned problems, and its objective is to provide a core-shell structured cathode active material, a manufacturing method for the cathode active material, a cathode plate, a secondary battery, a battery module, a battery pack, and a power consumption device, which solve the problems of conventional lithium manganese phosphate cathode active materials being prone to Li / Mn antisite defects during charge and discharge and relatively serious manganese elution, thereby solving the problems of low capacity, poor safety performance, and poor cycle performance of secondary batteries. [Means for solving the problem]

[0004] In order to achieve the above object, a first aspect of the present application provides a positive electrode active material having a core-shell structure, the positive electrode active material including a core and a shell covering the core, The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1, y is selected from any number in the range of 0.001-0.6, and optionally from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.1, n is selected from any number in the range of 0.001-0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; The shell includes a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein: The first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; a MP2O7 and M b (P2O7) cM is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and is optionally one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, and Al; The second coating layer is an oxide M' d O e wherein d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, M' is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, and optionally one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, S, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and more preferably one or more elements selected from Mg, Al, Ca, Ti, V, Co, Ni, Cu, Zn and Zr; The third coating layer includes carbon.

[0005] The inventors of the present application have found that in actual work, the lithium manganese phosphate positive electrode active material is prone to Li / Mn antisite defects during deep charging and discharging, and manganese leaching is relatively serious. The leached manganese is reduced to metal manganese after transitioning to the negative electrode. These generated metal manganese correspond to a "catalyst" and can catalyze the decomposition of the SEI film (solid electrolyte interphase) on the surface of the negative electrode. Some of the generated by-products are gases, which are prone to causing battery expansion and affecting the safety performance of the secondary battery, and another part is deposited on the surface of the negative electrode, obstructing the channel through which lithium ions enter and exit the negative electrode, resulting in an increase in the impedance of the secondary battery, and affecting the dynamic performance and cycle performance of the battery. In addition, in order to compensate for the lost SEI film, the electrolyte and active lithium inside the battery are constantly consumed, which has an irreversible effect on the capacity retention rate of the secondary battery.

[0006] Therefore, the applicant unexpectedly discovered that the lithium manganese phosphate core is obtained by doping the elements A, B, C, and D into the Li site, Mn site, P site, and O site of the lithium manganese phosphate, and the core surface is successively coated with three layers to provide a new type of core-shell structured positive electrode active material, which can greatly reduce the occurrence of Li / Mn antisite defects, significantly reduce the dissolution of manganese, reduce the lattice change rate, and increase the compaction density, and can be used in secondary batteries to improve the capacity of the secondary battery, and improve the cycle performance, high temperature storage performance, and safety performance of the secondary battery. Here, the oxide in the second coating layer has high structural stability and low surface activity, so that the second coating layer can effectively reduce the interface side reaction, thereby improving the high temperature cycle and high temperature storage performance of the battery.

[0007] As used herein, crystalline refers to a degree of crystallinity of 50% or more, i.e., 50%-100%. A degree of crystallinity of less than 50% is referred to as a glassy state.

[0008] The crystallinity of the crystalline pyrophosphate of the present application is 50% to 100%. A pyrophosphate with a certain crystallinity is not only advantageous for fully exerting the function of preventing the dissolution of manganese from the pyrophosphate coating layer and reducing the interfacial side reaction, but also can enable the pyrophosphate coating layer and the oxide coating layer to achieve better lattice matching, thereby realizing a tight bond between the coating layers.

[0009] Unless otherwise noted, the chemical formula is Li m A x Mn 1-y B y P 1-z C z O 4-n D nIn the above, when A is two or more elements, the above-mentioned limit on the numerical range of x not only limits the stoichiometric number of each type of element that constitutes A, but also limits the sum of the stoichiometric numbers of each element that constitutes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers x1, x2...xn of A1, A2...An must all be within the numerical range in which the application limits x, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C, and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C, and D in the present application also has the above-mentioned meaning.

[0010] Unless otherwise specified, the chemical formula M b (P2O7) c In the formula M', when M is two or more elements, the above-mentioned limit on the numerical range of b not only limits the stoichiometric number of each type of element that constitutes M, but also limits the sum of the stoichiometric numbers of each element that constitutes M. For example, when M is two or more elements M1, M2...Mn, the stoichiometric numbers b1, b2...bn of M1, M2...Mn must all be within the numerical range in which the present application limits b, and the sum of b1, b2...bn must also be within this numerical range. Similarly, the formula M' d O e When M′ in is two or more elements, the limitations of the numerical range of the stoichiometric number d of M′ in this application also have the above meaning.

[0011] In any embodiment of the first aspect, the lattice spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm and the angle of the (111) crystal direction is in the range of 18.00°-32.00°; Optionally, the lattice spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.300-0.310 nm; and / or The range of the angle with respect to the crystal direction (111) of the crystalline pyrophosphate in the first coating layer is 29.00°-30.00°.

[0012] The first coating layer in the positive electrode active material of the present application uses a crystalline material, and the range of the angle between the lattice spacing and the lattice spacing is within the above range, thereby effectively avoiding impurity phases in the coating layer, thereby increasing the gram capacity of the material and improving the cycle performance and rate performance of the secondary battery.

[0013] In any embodiment of the first aspect, x is any number in the range of 0.001-0.005; and / or y is any number in the range of 0.01-0.5, optionally any number in the range of 0.25-0.5; and / or z is any number in the range of 0.001-0.005, and / or n is any number in the range of 0.001-0.005.

[0014] Thus, x, y, z, and n are within the above ranges, which can further reduce the occurrence of Li / Mn antisite defects, reduce the elution of manganese, and reduce the lattice change rate, thereby further improving the capacity of the secondary battery, and improving the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.

[0015] In any embodiment of the first aspect, in the core, the ratio of 1-y to y is 0.67-999, optionally 1 to 4, more preferably 1.5 to 3, thereby further improving the cycle performance and rate performance of the secondary battery.

[0016] In any embodiment of the first aspect, in the core, the ratio of m to x is 9 to 1100, and optionally 190 to 998, thereby further improving the cycle performance and rate performance of the secondary battery.

[0017] In any embodiment of the first aspect, the carbon in the third coating layer is a mixture of SP2 and SP3 forms of carbon, and optionally the molar ratio of the SP2 and SP3 forms of carbon is any number in the range of 0.07-13, more optionally any number in the range of 0.1-10, and even more optionally any number in the range of 2.0-3.0.

[0018] The present application improves the overall performance of the secondary battery by limiting the molar ratio of SP2 form carbon to SP3 form carbon within the above range.

[0019] In any embodiment of the first aspect, the coverage of the first coating layer is greater than 0 and less than or equal to 6 wt.%, alternatively greater than 0 and less than or equal to 5.5 wt.%, and further alternatively greater than 0 and less than or equal to 2 wt.%, based on the weight of the core; and / or the coverage of the second coating layer is greater than 0 and less than 6 wt.%, alternatively greater than 0 and less than 5.5 wt.%, further alternatively 2 wt.%-4 wt.%, based on the weight of the core; and / or The coverage of the third coating layer is, based on the weight of the core, greater than 0 and not greater than 6 wt%, optionally greater than 0 and not greater than 5.5 wt%, and further optionally greater than 0 and not greater than 2 wt%.

[0020] In the positive electrode active material having a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above-mentioned range, so that the core can be sufficiently coated, and at the same time, the gram capacity of the positive electrode active material is not sacrificed, and the dynamic performance and safety performance of the secondary battery are further improved.

[0021] In any embodiment of the first aspect, the thickness of the first coating layer is 1-10 nm. In the present application, when the thickness of the first coating layer is in the range of 1-10 nm, the elution and transition of transition metal ions can be further reduced, and the dynamic performance of the secondary battery can be improved.

[0022] In any embodiment of the first aspect, the thickness of the second coating layer is 2-25 nm, and optionally 2-15 nm. When the thickness of the second coating layer is within the above range, the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so that the interface side reaction can be effectively reduced, thereby improving the high temperature performance of the secondary battery.

[0023] In any embodiment of the first aspect, the thickness of the third coating layer is 2-25 nm. When the thickness of the third coating layer is in the range of 2-25 nm, it can enhance the electrical conductivity performance of the material and improve the packing density performance of the battery plate manufactured using the positive electrode active material.

[0024] In an optional embodiment of the first aspect, based on the weight of the cathode active material, the content of elemental manganese is in the range of 10%-35% by weight, alternatively in the range of 13.3%-33.2% by weight, more preferably in the range of 15%-30% by weight, and even more preferably in the range of 17%-20% by weight; and / or The phosphorus content is in the range of 12%-25% by weight, preferably in the range of 15%-20% by weight, more preferably in the range of 16.8%-19.5% by weight; Preferentially, the weight ratio of elemental manganese to elemental phosphorus is in the range of 0.71-1.85, more preferably in the range of 0.90-1.25, and even more preferably in the range of 0.95-1.20.

[0025] In the core-shell structured positive electrode active material of the present application, the content of manganese element is within the above range, which can effectively improve the structural stability and density of the positive electrode active material, thereby improving the cycle, storage and compaction density performances of the secondary battery, and maintaining a certain voltage plateau height, thereby improving the energy density of the secondary battery.

[0026] In the positive electrode active material having a core-shell structure of the present application, the content of phosphorus element is within the above range, which can effectively improve the electrical conductivity of the positive electrode active material and can also improve the structural stability of the positive electrode active material.

[0027] In the positive electrode active material having a core-shell structure of the present application, the weight ratio of manganese to phosphorus is within the above range, which can reduce the elution of transition metals, thereby improving the stability of the positive electrode active material and the cycle and storage performance of the secondary battery, and can maintain a constant discharge voltage plateau height, thereby improving the energy density of the secondary battery.

[0028] In any embodiment of the first aspect, the lattice change rate of the positive electrode active material before and after complete desorption or absorption of lithium is 8.1% or less, optionally 4% or less, more optionally 3.8% or less, and further optionally 2.0%-3.8%.

[0029] The positive electrode active material having a core-shell structure of the present application can realize a lattice change rate before and after desorbing or absorbing lithium of 8.1% or less (optionally 4% or less), and therefore the gram capacity and rate performance of a secondary battery can be improved by using the positive electrode active material.

[0030] In any embodiment of the first aspect, the positive electrode active material has a Li / Mn antisite defect concentration of 4% or less, optionally 2.2% or less, and more preferably 1.5%-2.2%. By having the Li / Mn antisite defect concentration within the above range, Li + The transmission of the positive electrode active material can be improved, and the gram capacity of the positive electrode active material and the rate performance of the secondary battery can be improved.

[0031] In any embodiment of the first aspect, the positive electrode active material has a compacted density at 3 T of 1.98 g / cm 3 or more, and optionally 2.2 g / cm 3 More preferably, 2.2 g / cm 3 or more and 2.8 g / cm 3As a result, if the compaction density is improved and the weight of the positive electrode active material per unit volume is increased, this is advantageous for improving the volumetric energy density of the secondary battery.

[0032] In any embodiment of the first aspect, the valence state of the surface oxygen of the positive electrode active material is -1.90 or less, and optionally -1.90 to -1.98. By limiting the valence state of the surface oxygen of the positive electrode active material to the above range, it is possible to reduce the interfacial side reaction between the positive electrode material and the electrolyte, thereby improving the performance of the battery core, such as cycle and high-temperature storage gas generation.

[0033] A second aspect of the present application provides a method for producing a positive electrode active material, the method comprising the steps of: Providing a core material, the core material comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1, y is selected from any number in the range of 0.001-0.6, and optionally from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.1, n is selected from any number in the range of 0.001-0.1, and A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally from Al, Mg, Nb, Mo and W. B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; Li pyrophosphate a MP2O7 and / or M b (P2O7) c a first coating step of mixing a core material with the first mixture, drying and sintering to obtain a material coated with a first coating layer, wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; a MP2O7 and M b (P2O7) c a first coating step in which M is each independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr and Al; Oxide M' d O e a second coating step of mixing the material to be coated with the first coating layer with the second mixture, drying and sintering to obtain a material to be coated with two coating layers, wherein d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, and M′ is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, and optionally Li, Be. a second coating step with one or more elements selected from the group consisting of B, Na, Mg, Al, Si, P, S, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, more preferentially with one or more elements selected from the group consisting of Mg, Al, Ca, Ti, V, Co, Ni, Cu, Zn and Zr; providing a third mixture containing a carbon source, mixing a material to be coated with the two coating layers with the third mixture, drying and sintering the material to be coated with the two coating layers to obtain a positive electrode active material; Here, the positive electrode active material has a core-shell structure, which includes a core and a shell covering the core, and the core is Lim A x Mn 1-y B y P 1-z C z O 4-n D n the shell includes a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, the first coating layer being made of crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c and the second coating layer comprises an oxide M' d O e and the third coating layer comprises carbon.

[0034] Therefore, the present application provides a doped lithium manganese phosphate core by doping the elements A, B, C, and D into the Li site, manganese site, phosphorus site, and O site of lithium manganese phosphate, and then sequentially coating the surface of the core with three layers to provide a new type of core-shell structured cathode active material, which can greatly reduce the occurrence of Li / Mn antisite defects, significantly reduce the dissolution of manganese, reduce the lattice change rate, and increase the compaction density, and can be used in secondary batteries to improve the capacity of the secondary batteries, and improve the cycle performance, high-temperature storage performance, and safety performance of the secondary batteries.

[0035] In any embodiment of the second aspect of the present application, the step of providing a core material comprises: (1) mixing a source of manganese, a source of element B, an acid and a selective solvent to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, and a source of element D, and an optional solvent, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

[0036] In any embodiment of the second aspect of the present application, step (1) comprises mixing at 60° C.-120° C. and / or mixing in step (1) with stirring at a rotation speed of 200-800 rpm.

[0037] In any embodiment of the second aspect of the present application, in step (2), the mixing is carried out for 8-15 hours.

[0038] In any embodiment of the second aspect of the present application, in step (2), sintering is carried out at 600° C.-900° C. for 6-14 hours.

[0039] In any embodiment of the second aspect of the present application, In a first coating step, a first mixture is obtained by mixing a source of element M, a phosphorus source, an acid, an optional lithium source with an optional solvent, and / or In a second coating step, a second mixture is obtained by mixing a source of element M′ with a solvent, and / or In a third coating step, a third mixture is obtained by mixing a carbon source with a solvent.

[0040] In an optional embodiment of the second aspect of the present application, in the first coating step, the source of element M, the phosphorus source, the acid, the optional lithium source and the optional solvent are mixed at room temperature for 1-5 h, then heated to 50° C.-120° C. and maintained at this temperature for 2-10 h, all at a pH of 3.5-6.5.

[0041] In an optional embodiment of the second aspect of the present application, in the second coating step, the source of element M′ and the solvent are mixed at room temperature for 1-10 h, then heated to 60° C.-150° C. and maintained at this temperature for 2-10 h.

[0042] In an optional embodiment of the second aspect of the present application, the source of element A is one or more selected from the group consisting of an element A, an oxide, a phosphate, an oxalate, a carbonate and a sulfate, and / or the source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The source of element D is one or more selected from a simple substance of element D and an ammonium salt thereof.

[0043] In any embodiment of the second aspect of the present application, in the first coating step, sintering is performed at 650-800° C. for 2-6 hours; and / or In the second coating step, sintering is performed at 500-700° C. for 6-10 hours; and / or In the third coating step, sintering is carried out at 700-800° C. for 6-10 hours.

[0044] A third aspect of the present application provides a positive electrode plate, the positive electrode plate including a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the production method of the second aspect of the present application, and optionally, the content of the positive electrode active material in the positive electrode film layer is 90-99.5 wt %, more optionally 95-99.5 wt %, based on the total weight of the positive electrode film layer.

[0045] A fourth aspect of the present application provides a secondary battery, the secondary battery including the positive electrode active material of the first aspect of the present application or the positive electrode active material produced by the production method of the second aspect of the present application or the positive electrode plate of the third aspect of the present application.

[0046] A fifth aspect of the present application provides a battery module, the battery module including the secondary battery of the fourth aspect of the present application.

[0047] A sixth aspect of the present application provides a battery pack, the battery pack including the battery module of the fifth aspect of the present application.

[0048] A seventh aspect of the present application provides a power consumption device, the power consumption device including at least one selected from a secondary battery of the fourth aspect of the present application, a battery module of the fifth aspect of the present application, and a battery pack of the sixth aspect of the present application. [Brief description of the drawings]

[0049] [Figure 1] FIG. 2 is a schematic diagram of a positive electrode active material having a three-layer coating structure according to an embodiment of the present application. [Diagram 2] 1 is a schematic diagram of a secondary battery according to an embodiment of the present application; [Diagram 3] FIG. 3 is an exploded view of the secondary battery according to the embodiment of the present application shown in FIG. 2. [Figure 4] 1 is a schematic diagram of a battery module according to an embodiment of the present application; [Diagram 5] 1 is a schematic diagram of a battery pack according to an embodiment of the present application; [Figure 6] FIG. 6 is an exploded view of the battery pack according to the embodiment of the present application shown in FIG. 5. [Figure 7] 1 is a schematic diagram of a power consumption device that uses a secondary battery as a power source according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0050] Hereinafter, with reference to the drawings, embodiments specifically disclosing the positive electrode active material, the method for manufacturing the positive electrode active material, the positive electrode plate, the secondary battery, the battery module, the battery pack, and the power consumption device of the present application will be described in detail. However, unnecessary detailed description may be omitted. For example, detailed description of well-known matters and duplicated description of the same structure may be omitted. This is to avoid the following description from becoming unnecessarily long and to allow those skilled in the art to easily understand. Note that the drawings and the following description are provided to allow those skilled in the art to fully understand the present application, and are not intended to limit the subject matter described in the claims.

[0051] The "ranges" disclosed in this application are defined in the form of lower and upper limits, and a given range is defined by selecting one lower limit and one upper limit, and the selected lower and upper limits define the boundaries of the particular range. Such defined ranges may be inclusive or exclusive of the extreme values, and may be arbitrarily combined, i.e., any lower limit may be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also envisaged. However, if 1 and 2 are listed as minimum range values, and 3, 4, and 5 are listed as maximum range values, the ranges 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5 are all envisaged. In this application, unless otherwise specified, the numerical range "ab" represents a shorthand representation of any combination of real numbers from a to b, where a and b are both real numbers. For example, the numerical range "0-5" represents a list of all real numbers between "0-5" already listed in this specification, and "0-5" is just a shorthand representation of combinations of these numbers. Also, expressing a parameter as an integer ≧2 is equivalent to disclosing that the parameter is, for example, the integers 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0052] In this application, the ranges "less than or equal to a certain value" and "greater than or equal to a certain value" refer to ranges defined by a certain value as the upper or lower limit.

[0053] Unless otherwise stated, all the embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0054] Unless otherwise stated, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0055] Unless otherwise stated, all steps in this application may be performed in sequence or randomly, preferably in sequence. For example, a method including steps (a) and (b) means that the method may include steps (a) and (b) performed in sequence, or may include steps (b) and (a) performed in sequence. For example, a method described may further include step (c) means that step (c) may be added to the method in any order, e.g., the method may include steps (a), (b) and (c), may include steps (a), (c) and (b), may include steps (c), (a) and (b), etc.

[0056] Unless otherwise stated, the terms "comprise" and "comprises" referred to in this application may be open ended or closed ended. For example, "comprise" and "comprises" may further include or include other ingredients not listed, or may include or include only the listed ingredients.

[0057] Unless otherwise stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, "A or B" is satisfied if A is true (or exists) and B is false (or does not exist), if A is false (or does not exist) but B is true (or exists), or if both A and B are true (or exist).

[0058] Unless otherwise stated, in this application, the term "coating layer" refers to a layer of material that is coated on a core, and the layer of material may completely or partially cover the core, and the use of "coating layer" is for ease of description and is not intended to limit the invention.

[0059] Unless otherwise specified, in this application, the term "thickness of a coating layer" refers to the thickness of a material layer coating a core in the radial direction of the core.

[0060] [Secondary battery] A secondary battery is also called a rechargeable battery or storage battery, and is a battery that can be continuously used by activating the active material by charging after discharging the battery.

[0061] Generally, a secondary battery includes a positive electrode plate, a negative electrode plate, a separator, and an electrolyte. During charging and discharging of the battery, active ions (e.g., lithium ions) shuttle between the positive electrode plate and the negative electrode plate to absorb and release. The separator is disposed between the positive electrode plate and the negative electrode plate, and mainly serves to prevent short-circuiting between the positive and negative electrodes, while allowing the active ions to pass through. The electrolyte mainly serves to conduct the active ions between the positive electrode plate and the negative electrode plate.

[0062] [Cathode active material] The present application provides a positive electrode active material having a core-shell structure, the positive electrode active material including a core and a shell covering the core, The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D nwherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1 (e.g., 0.002, 0.003, 0.005, 0.05), y is selected from any number in the range of 0.001-0.6, and optionally from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.1 (e.g., 0.005, 0.04, 0.05, 0.08), n is selected from any number in the range of 0.001-0.1 (e.g., 0.002, 0.005, 0.01, 0.05, 0.08), and A is Zn, Al, Na, K, Mg, Nb , Mo and W, and optionally one or more elements selected from Al, Mg, Nb, Mo and W; B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; The shell includes a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein: The first coating layer is crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; a MP2O7 and M b (P2O7) c M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al, and is optionally one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, and Al; The second coating layer is an oxide M' d O e (Optionally, crystalline oxide M' d O e where d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, M' is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, and optionally one or more elements selected from Li, Be, B, Na, Mg, Al, Si, P, S, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, and more preferably one or more elements selected from Mg, Al, Ca, Ti, V, Co, Ni, Cu, Zn and Zr; The third coating layer includes carbon.

[0063] The positive electrode active material of the present application can improve the gram capacity, cycle performance and safety performance of the secondary battery. Although the mechanism is not yet clear, it is speculated as follows. The positive electrode active material of the present application has a core-shell structure, in which the elements A, B, C and D are respectively doped into the Li site, manganese site, phosphorus site and O site of the lithium manganese phosphate core, which can effectively reduce the elution of manganese, further reduce the manganese ions transferred to the negative electrode, reduce the electrolyte consumed by the decomposition of the SEI film, and not only improve the cycle performance and safety performance of the secondary battery, but also promote the adjustment of Mn-O bonds, reduce the lithium ion transition barrier, promote lithium ion transition, and improve the rate performance of the secondary battery, and the first coating layer containing crystalline pyrophosphate on the core. By coating, the transition resistance of manganese can be further increased, its elution can be reduced, and the content of heterolithium on the surface can be reduced, thereby reducing the contact between the core and the electrolyte, thereby reducing the interfacial side reaction, reducing gas generation, and improving the high-temperature storage performance, cycle performance and safety performance of the secondary battery; by further coating with a highly stable oxide coating layer, the interfacial side reaction on the surface of the positive electrode active material can be effectively reduced, thereby further improving the high-temperature cycle and storage performance of the secondary battery; by further coating with a carbon layer as a third coating layer, the safety performance and dynamic performance of the secondary battery can be further improved. In addition, in the core, the lattice change rate is reduced by doping Li and Mn sites, and the Mn site doping can further effectively reduce the surface activity, thereby suppressing the dissolution of Mn and the interfacial side reaction between the positive electrode active material and the electrolyte; the P site doping can make the change rate of the Mn-O bond length more rapid and reduce the small polaron transition barrier of the material, thereby benefiting the electronic conductivity; the O site doping has a good effect on reducing the interfacial side reaction; the P site and O site doping can further affect the dissolution of Mn of antisite defects and the dynamic performance, so the doping can reduce the concentration of antisite defects in the material, improve the dynamic performance and gram capacity of the material, and even change the particle topography, thereby increasing the compaction density.

[0064] Unless otherwise noted, the chemical formula is Li m A x Mn 1-y B y P 1-z C z O 4-n D n In the above, when A is two or more elements, the above-mentioned limit on the numerical range of x not only limits the stoichiometric number of each type of element that constitutes A, but also limits the sum of the stoichiometric numbers of each element that constitutes A. For example, when A is two or more elements A1, A2...An, the stoichiometric numbers x1, x2...xn of A1, A2...An must all be within the numerical range in which the application limits x, and the sum of x1, x2...xn must also be within this numerical range. Similarly, when B, C, and D are two or more elements, the limit on the numerical range of the stoichiometric numbers of B, C, and D in the present application also has the above-mentioned meaning.

[0065] In some embodiments, when A is one, two, three or four elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A x Q x1 H x2 E x3 K x4 where x1+x2+x3+x4=x, and x1, x2, x3, and x4 are all positive numbers and not zero at the same time, and Q, H, E, and K are each independently one selected from Zn, Al, Na, K, Mg, Nb, Mo, and W. Alternatively, one of x1, x2, x3, and x4 is zero and the remaining is not zero, more preferably, two of x1, x2, x3, and x4 are zero and the remaining is not zero, more preferably, three of x1, x2, x3, and x4 are zero and the remaining is not zero. Core Li m A x Mn 1-y B y P 1-z C z O 4-n D nIn the present invention, it is advantageous to dope one, two, three or four of the above A elements into the Li site, and selectively dope one, two or three of the above A elements into the Mn site, one or two B elements into the Phosphorus site, and one or two C elements into the O site, which are advantageous for uniformly distributing the doping elements.

[0066] In some embodiments, the values ​​of m, x, y, z and n satisfy the requirement to maintain electrical neutrality throughout the core.

[0067] Core Li m A x Mn 1-y B y P 1-z C z O 4-n D n In this, the magnitude of m is influenced by the magnitude of the valence states of A, B, C, D and the magnitudes of x, y, z and n to ensure that the whole system exhibits electrical neutrality. If the value of m is too small, it will cause the lithium content of the whole core system to be reduced, affecting the gram capacity of the material. The values ​​of x, y, z, and n limit the total amount of all doping elements, and if the doping amount is too small, the doping element will not function, and if y is more than 0.6, it will cause the content of Mn in the system to be low, affecting the voltage plateau of the material. The C element is doped at the P position, and the PO tetrahedron is relatively stable, but if the z value is too large, it will affect the stability of the material, so the z value is limited to 0.001-0.1.

[0068] In addition, maintaining the electrical neutrality of the entire core system can ensure that defects and heterophases in the positive electrode active material are minimized. When an excess transition metal (e.g., manganese) is present in the positive electrode active material, the structure of the material system itself is relatively stable, and the excess transition metal is likely to precipitate in the form of an element or form a heterophase inside the lattice, and by maintaining electrical neutrality, such heterophases can be minimized. In addition, ensuring the electrical neutrality of the system can also improve the kinetic performance of the material by generating lithium vacancies in the material in some cases.

[0069] Process control (e.g., thoroughly mixing and grinding various source materials) can ensure that each element is uniformly distributed in the lattice without aggregation. The main feature peak position in the XRD diagram of lithium manganese phosphate after element doping is consistent with that of undoped LiMnPO4, indicating that no impurity phase is introduced in the doping process, so the improvement of core performance is mainly due to element doping, not heterophase. After the positive electrode active material is produced, the inventor of the present application cuts out the middle region of the already produced positive electrode active material particles by focused ion beam (abbreviated as FIB), and tests it by transmission electron microscope (abbreviated as TEM) and X-ray spectroscopy (abbreviated as EDS), and found that each element is uniformly distributed without aggregation.

[0070] In some embodiments, the values ​​of a, b, c, d and e are the same as those of the crystalline Li pyrophosphate. a MP2O7 or M b (P2O7) c and M′ d O e The condition of maintaining electrical neutrality is met.

[0071] In some embodiments, the crystallinity refers to a crystallinity of 50% or more, i.e., 50%-100%. A crystallinity of less than 50% is referred to as a glass state. The crystallinity of the crystalline pyrophosphate of the present application is 50% to 100%. A pyrophosphate with a certain crystallinity is not only advantageous for fully exerting the function of preventing the dissolution of manganese from the pyrophosphate coating layer and reducing the interfacial side reaction, but also allows the pyrophosphate coating layer and the oxide coating layer to have a better lattice match, thereby realizing a tighter bond between the coating layers.

[0072] In some embodiments, the crystallinity of the crystalline pyrophosphate of the first coating layer material of the positive electrode active material may be tested by common technical means in the art, such as density methods, infrared spectroscopy, differential scanning calorimetry, and nuclear magnetic resonance spectroscopy, and may also be tested by, for example, X-ray diffraction methods.

[0073] A specific method for testing the crystallinity of the first coating layer crystalline pyrophosphate of the positive electrode active material by X-ray diffraction may include the following steps.

[0074] A certain amount of positive electrode active material powder is taken and the total scattering intensity is measured by X-ray, which is the sum of the scattering intensity of the material in the entire space and has nothing to do with the order state of the sample, but only with the intensity of the primary radiation, the chemical structure of the positive electrode active material powder, and the total number of electrons involved in diffraction, i.e., the amount of mass. Crystalline scattering and non-crystalline scattering are separated from the diffraction pattern, and the crystallinity is the ratio of the crystalline partial scattering to the total scattering intensity.

[0075] It should be noted that in some embodiments, the crystallinity of the pyrophosphate in the coating layer can be adjusted, for example, by adjusting the process conditions of the sintering process, such as sintering temperature, sintering time, and the like.

[0076] In some embodiments, the pyrophosphate can be used as a first coating layer to effectively isolate the doping metal ions from the electrolyte, since the metal ions are less likely to transition through the pyrophosphate. The crystalline pyrophosphate coating can effectively inhibit the elution of the transition metals and improve the cycle performance, since the structure of the crystalline pyrophosphate is stable.

[0077] In some embodiments, the bond between the first coating layer and the core is similar to a heterojunction, and the strength of the bond is limited by the degree of lattice matching. When the lattice mismatch is less than 5%, the lattice matching is relatively good, and the two are likely to be tightly bonded. The tight bond can ensure that the coating layer does not fall off in the subsequent cycle process, which is favorable for ensuring the long-term stability of the material. The degree of bonding between the first coating layer and the core is mainly determined by calculating the mismatch between the core and each lattice coating constant. In the present application, after doping the core with an element, the matching between the core and the first coating layer is improved, compared with not doping the element, and the core and the pyrophosphate coating layer can be more tightly bonded together.

[0078] The reason why oxide is selected as the second coating layer is that, firstly, it has a relatively high lattice match with the first coating crystalline pyrophosphate (mismatch is only 3%), and secondly, the stability of the oxide itself is better than that of pyrophosphate, so that using it to coat pyrophosphate is advantageous for improving the stability of the material. Because the structure of the oxide is very stable, using the oxide for coating can effectively reduce the interfacial side reaction on the surface of the positive electrode active material, thereby improving the high-temperature cycle and storage performance of the secondary battery. The lattice matching manner between the second coating layer and the first coating layer is similar to the bonding situation between the first coating layer and the core, and when the lattice mismatch is less than 5%, the lattice matching is relatively good and both are easy to bond tightly.

[0079] The main reason for using carbon as the third coating layer is that the carbon layer has relatively good electronic conductivity. When applied to secondary batteries, electrochemical reactions occur and require the participation of electrons, so carbon with excellent electrical conductivity can be used for coating to increase the electronic transmission between particles and between different positions on the particles. Carbon coating can effectively improve the electrical conductivity and desolvation ability of the positive electrode active material.

[0080] FIG. 1 is a schematic diagram of a positive electrode active material with an ideal three-layer coating structure. As shown in the figure, the innermost circle exemplarily represents the core, and from the inside to the outside, the first coating layer, the second coating layer, and the third coating layer are arranged in this order. This figure represents an ideal state in which each layer is completely coated, and in practice, each coating layer may be completely or partially coated.

[0081] In some embodiments, the lattice spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm and the angle of the (111) crystal direction is in the range of 18.00°-32.00°; Optionally, the lattice spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.300-0.310 nm (e.g., 0.303 nm); and / or The range of the angle formed by the crystal direction (111) of the crystalline pyrophosphate in the first coating layer is 29.00°-30.00° (e.g., 29.496°).

[0082] The crystalline pyrophosphate in the first coating layer may be characterized by techniques common in the art, such as by transmission electron microscopy (TEM), which allows the core and coating layers to be distinguished by examining the lattice spacing.

[0083] A specific method for testing the angle between the lattice spacing of the crystalline pyrophosphate in the first coating layer may include the following steps.

[0084] A certain amount of coated positive active material sample powder is taken into a test tube, and a solvent, such as alcohol, is poured into the test tube and thoroughly stirred to disperse it. Then, a proper amount of the above solution is taken and dropped onto a 300 mesh copper net using a clean disposable plastic straw, at this time, some of the powder remains on the copper net, and the copper net together with the sample is transferred to the TEM sample cavity for testing, and the original image of the TEM test is obtained and the original image is preserved.

[0085] The original image obtained in the above TEM test is opened in the diffraction instrument software and a Fourier transform is performed to obtain the diffraction pattern. By measuring the distance from the diffraction spot to the center position in the diffraction pattern, the lattice spacing can be obtained, and the angle formed can be calculated using the Bragg equation.

[0086] A crystalline pyrophosphate within the above-mentioned lattice spacing and angle range can more effectively suppress the lattice change rate of lithium manganese phosphate and the elution of Mn during the process of releasing or absorbing lithium, thereby improving the high-temperature cycle performance, cycle stability and high-temperature storage performance of the secondary battery.

[0087] In some embodiments, x is any number in the range of 0.001-0.005; and / or y is any number in the range of 0.01-0.5, optionally any number in the range of 0.25-0.5; and / or z is any number in the range of 0.001-0.005, and / or n is any number in the range of 0.001-0.005.

[0088] Thus, x, y, z, and n are within the above ranges, which can further reduce the occurrence of Li / Mn antisite defects, reduce the elution of manganese, and reduce the lattice change rate, thereby further improving the capacity of the secondary battery, and improving the cycle performance, high-temperature storage performance, and safety performance of the secondary battery.

[0089] In some embodiments, in the core, the ratio of 1-y to y is 0.67-999, preferably 1-4, more preferably 1.5-3, thereby further improving the cycle performance and rate performance of the secondary battery. Here, y represents the sum of the stoichiometric number of the doping element B at the Mn site. When the above conditions are satisfied, the energy density and cycle performance of the secondary battery using the positive electrode active material can be further improved.

[0090] In some embodiments, the ratio of m to x in the core is 9 to 1100, and optionally 190 to 998, where z represents the sum of the stoichiometric numbers of the doping element C in the P site. When the above conditions are met, the energy density and cycle performance of the secondary battery using the positive electrode active material can be further improved.

[0091] In some embodiments, the carbon in the third coating layer is a mixture of SP2 and SP3 forms of carbon, and optionally the molar ratio of the SP2 and SP3 forms of carbon is any number in the range of 0.07-13, more preferably any number in the range of 0.1-10, and even more preferably any number in the range of 2.0-3.0.

[0092] In some embodiments, the molar ratio of carbon in the SP2 form to carbon in the SP3 form can be about 0.1, about 0.2, about 0.3, about 0.4, about 0.5, about 0.6, about 0.7, about 0.8, about 0.9, about 1, about 2, about 3, about 4, about 5, about 6, about 7, about 8, about 9, or about 10, or within any range of any of the above values.

[0093] In this application, the term "about" a certain value denotes a range, representing a range of ±10% of that value.

[0094] The carbon morphology in the carbon coating layer is selected to improve the overall electrical performance of the secondary battery. Specifically, by using a mixture of SP2 carbon and SP3 carbon and restricting the ratio of SP2 carbon to SP3 carbon to a certain range, good electrical conductivity can be achieved and the passage of lithium ions can be guaranteed, which is favorable for the realization of the secondary battery function and its cycle performance.

[0095] The mixture ratio of the SP2 form and the SP3 form of the carbon in the third coating layer can be controlled by the sintering conditions, such as the sintering temperature and the sintering time. For example, when the third coating layer is manufactured using sucrose as a carbon source, the sucrose is decomposed at high temperature, and then deposited on the second coating layer, and at the same time, a carbon coating layer having both the SP3 form and the SP2 form is generated by the action of high temperature. The ratio of the SP2 form carbon and the SP3 form carbon can be controlled by selecting the high temperature decomposition conditions and the sintering conditions.

[0096] The structure and characteristics of the third coating layer carbon can be measured by Raman spectroscopy. A specific test method is to perform peak splitting on the energy spectrum of the Raman test to obtain Id / Ig (where Id is the peak intensity of SP3 form carbon and Ig is the peak intensity of SP2 form carbon), thereby confirming the molar ratio of both.

[0097] In some embodiments, the coverage of the first coating layer is greater than 0 and less than or equal to 6 wt.%, alternatively greater than 0 and less than or equal to 5.5 wt.%, and further alternatively greater than 0 and less than or equal to 2 wt.%, based on the weight of the core; and / or the coverage of the second coating layer is greater than 0 and less than 6 wt.%, alternatively greater than 0 and less than 5.5 wt.%, further alternatively 2 wt.%-4 wt.%, based on the weight of the core; and / or The coverage of the third coating layer is, based on the weight of the core, greater than 0 and not greater than 6 wt%, optionally greater than 0 and not greater than 5.5 wt%, and further optionally greater than 0 and not greater than 2 wt%.

[0098] In the present application, the coverage of each layer is not zero.

[0099] In the positive electrode active material having a core-shell structure of the present application, the coating amount of the three coating layers is preferably within the above-mentioned range, so that the core can be sufficiently coated, and at the same time, the gram capacity of the positive electrode active material is not sacrificed, and the dynamic performance and safety performance of the secondary battery are further improved.

[0100] For the first coating layer, by ensuring that the coating amount is within the above range, it is possible to reduce the elution of transition metals and ensure smooth transition of lithium ions, thereby improving the rate performance of the positive electrode active material.

[0101] For the second coating layer, by ensuring that the coating amount is within the above range, it is possible to maintain a constant plateau voltage for the positive electrode active material and ensure the coating effect.

[0102] As for the third coating layer, the carbon coating mainly plays the role of reinforcing the electron transmission between particles, but since a large amount of amorphous carbon is further contained in the structure, the density of the carbon is relatively low, and the coating amount within the above range can ensure the compaction density of the electrode plate.

[0103] In some embodiments, the thickness of the first coating layer is 1-10 nm; and / or the thickness of the second coating layer is 2-25 nm, optionally 2-15 nm; and / or The thickness of the third coating layer is 2-25 nm.

[0104] In some embodiments, the thickness of the first coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, or about 10 nm, or any range of any of the above numerical values.

[0105] In some embodiments, the thickness of the second coating layer can be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, or any range of any of the numerical values ​​recited above.

[0106] In some embodiments, the thickness of the third coating layer may be about 2 nm, about 3 nm, about 4 nm, about 5 nm, about 6 nm, about 7 nm, about 8 nm, about 9 nm, about 10 nm, about 11 nm, about 12 nm, about 13 nm, about 14 nm, about 15 nm, about 16 nm, about 17 nm, about 18 nm, about 19 nm, about 20 nm, about 21 nm, about 22 nm, about 23 nm, about 24 nm, or about 25 nm, or any range therebetween.

[0107] When the thickness of the first coating layer is in the range of 1-10 nm, it can effectively reduce the elution of transition metals and ensure the dynamic performance of the secondary battery.

[0108] When the thickness of the second coating layer is within the above range, the surface structure of the second coating layer is stable and the side reaction with the electrolyte is small, so that the interfacial side reaction can be effectively reduced, thereby improving the high-temperature performance of the secondary battery.

[0109] When the thickness of the third coating layer is in the range of 2-25 nm, it can enhance the electrical conductivity of the material and improve the compaction performance of the battery plate manufactured using the positive electrode active material.

[0110] The thickness and size of the coating layer are mainly tested by FIB, and the specific method may include the following steps: randomly select a single particle from the positive electrode active material powder to be tested, cut a slice with a thickness of about 100 nm from the middle position or near the middle position of the selected particle, and perform a TEM test on the slice to measure the thickness of the coating layer, measuring 3-5 positions and taking the average value.

[0111] In some embodiments, based on the weight of the positive electrode active material, the elemental manganese content is in the range of 10 wt%-35 wt%, optionally in the range of 13.3 wt%-33.2 wt%, more preferably in the range of 15 wt%-30 wt%, and further preferably in the range of 17 wt%-20 wt%, and / or the elemental phosphorus content is in the range of 12 wt%-25 wt%, optionally in the range of 15 wt%-20 wt%, and more preferably in the range of 16.8 wt%-19.5 wt%, and / or the weight ratio of elemental manganese to elemental phosphorus is in the range of 0.71-1.85, more preferably in the range of 0.90-1.25, and further preferably in the range of 0.95-1.20.

[0112] In the present application, when only manganese is contained in the core of the positive electrode active material, the manganese content can correspond to the content of the core.

[0113] In the present application, the manganese element content is limited within the above range, which can ensure that the stability and density of the positive electrode active material are relatively high, thereby improving the cycle, storage and compaction performance of the secondary battery, and maintaining a certain voltage plateau height, thereby improving the energy density of the secondary battery.

[0114] In the present application, the content of phosphorus element is limited within the above range, which can effectively improve the electrical conductivity of the material and enhance the overall stability of the material.

[0115] The weight ratio of the manganese and phosphorus contents within the above range can effectively reduce the elution of the transition metal manganese, improve the stability and gram capacity of the positive electrode active material, and further enhance the cycle performance and storage performance of the secondary battery, while contributing to reducing the heterophase in the material and maintaining the discharge voltage plateau height of the material, thereby improving the energy density of the secondary battery.

[0116] The manganese and phosphorus elements can be measured by using the general technical means in this field. In particular, the following method is used to measure the manganese and phosphorus contents: the material is dissolved in dilute hydrochloric acid (concentration 10-30%), and the content of each element in the solution is tested by ICP, and the manganese content is measured and converted to obtain its weight ratio.

[0117] In some embodiments, the lattice change rate of the positive electrode active material having a core-shell structure before and after complete lithium absorption or desorption is 8.1% or less, optionally 4% or less, more preferably 3.8% or less, and further preferably 2.0-3.8%.

[0118] The process of lithium manganese phosphate (LiMnPO4) releasing or absorbing lithium is a two-phase reaction. The interfacial stress between the two phases is determined by the magnitude of the lattice change rate before and after lithium is released or absorbed. The smaller the lattice change rate and the smaller the interfacial stress, the greater the Li + Therefore, reducing the lattice change rate of the core is + This is advantageous for reinforcing the transmission ability of the secondary battery, thereby improving the rate performance of the secondary battery. The positive electrode active material having a core-shell structure of the present application can realize a lattice change rate of 8.1% or less (optionally 4% or less) before and after desorbing or absorbing lithium, so that the rate performance of the secondary battery can be improved by using the positive electrode active material. The lattice change rate can be measured by a method known in the art, for example, X-ray diffraction spectrum (XRD).

[0119] In some embodiments, the Li / Mn antisite defect concentration of the core-shell structured cathode active material is 4% or less, alternatively 2.2% or less, more preferably 1.5-2.2%.

[0120] The Li / Mn antisite defect of the present application is Li + and Mn 2+ Accordingly, the Li / Mn antisite defect concentration is 2+ Compatible with Li + Li + It refers to a percentage occupying the total amount. In this application, the Li / Mn antisite defect concentration can be tested, for example, according to JIS K 0131-1996.

[0121] The positive electrode active material having the core-shell structure of the present application can realize the above-mentioned relatively low Li / Mn antisite defect concentration. Although the mechanism is not yet fully clear, the inventors of the present application believe that in the LiMnPO4 lattice, + and Mn 2+ The position is interchangeable with Li + Since the transmission channel is one-dimensional, Mn 2+ Li + It is difficult to change channels, and Li + Therefore, the positive electrode active material having a core-shell structure of the present application has a relatively low Li / Mn antisite defect concentration within the above range, and therefore Mn 2+ Li hindered by + The transmission of charge can be reduced, and the gram capacity and rate performance of the positive electrode active material can be improved.

[0122] In some embodiments, the positive electrode active material has a compacted density at 3 T of 1.98 g / cm 3 or more, and optionally 2.2 g / cm 3 More preferably, 2.2 g / cm 3 or more and 2.8 g / cm 3The higher the compaction density, the greater the weight of active material per unit volume, so improving the compaction density is beneficial to improving the volumetric energy density of the battery core. The compaction density can be measured according to GB / T 24533-2009.

[0123] In some embodiments, the surface oxygen valence state of the positive electrode active material is less than or equal to -1.90, and optionally between -1.90 and -1.98.

[0124] The stable valence state of oxygen is originally -2, and the closer the valence state is to -2, the stronger its electron-capturing ability becomes, i.e., the stronger its oxidizing property becomes, and generally, the valence state of the surface is -1.7 or less. As described above, the present application limits the valence state of the surface oxygen of the positive electrode active material to the above range, thereby reducing the interfacial side reaction between the positive electrode material and the electrolyte, thereby improving the performance of the battery core, such as cycle and high-temperature storage gas generation.

[0125] The surface oxygen valence state can be measured by methods known in the art, for example, by electron energy loss spectroscopy (EELS).

[0126] In some embodiments, m may be any number selected from the range of 0.97-1.01.

[0127] In some embodiments, y may be any number selected within the range of 0.25-0.5.

[0128] In some embodiments, a may be any number selected from the range of 1-2, for example 1, 2.

[0129] In some embodiments, b can be 1, 2, 3, 4, for example.

[0130] In some embodiments, c may be 1, 2, 3, for example.

[0131] In some embodiments, d may be any number selected from the range of 1-2, for example 1, 2.

[0132] In some embodiments, e may be any number selected from the range of 1-5, such as 1, 2, 3, 4, 5.

[0133] [Method of manufacturing positive electrode active material] The present application provides a method for producing a positive electrode active material, the method for producing the positive electrode active material comprising: Providing a core material, the core material comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1, y is selected from any number in the range of 0.001-0.6, and optionally from any number in the range of 0.001-0.5, z is selected from any number in the range of 0.001-0.1, n is selected from any number in the range of 0.001-0.1, and A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, and optionally from Al, Mg, Nb, Mo and W. B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, and optionally one or more elements selected from Ti, V, Fe, Ni, Mg and Co; C is one or more elements selected from B, S, Si and N, and optionally one or more elements selected from S, Si and N; D is one or more elements selected from S, F, Cl and Br, and optionally one or more elements selected from F, Cl and Br; Li pyrophosphate a MP2O7 and / or M b (P2O7) ca first coating step of mixing a core material with the first mixture, drying and sintering to obtain a material coated with a first coating layer, wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; a MP2O7 and M b (P2O7) c a first coating step in which M is each independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al, and optionally one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr and Al; Oxide M' d O e a second coating step of mixing the material to be coated with the first coating layer with the second mixture, drying and sintering to obtain a material to be coated with two coating layers, wherein d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, and M′ is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides and Sb, and optionally Li, Be. a second coating step with one or more elements selected from the group consisting of B, Na, Mg, Al, Si, P, S, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Se, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, W, La and Ce, more preferentially with one or more elements selected from the group consisting of Mg, Al, Ca, Ti, V, Co, Ni, Cu, Zn and Zr; providing a third mixture containing a carbon source, mixing a material to be coated with the two coating layers with the third mixture, drying and sintering the material to be coated with the two coating layers to obtain a positive electrode active material; Here, the positive electrode active material has a core-shell structure, which includes a core and a shell covering the core, and the core is Li m A x Mn 1-y B y P 1-z C zO 4-n D n the shell includes a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, the first coating layer being made of crystalline Li pyrophosphate. a MP2O7 and / or M b (P2O7) c and the second coating layer comprises an oxide M' d O e and the third coating layer comprises carbon, where A, B, C, D, M, M', m, x, y, z, n, a, b, c, d and e are defined as above.

[0134] Therefore, the present application provides a doped lithium manganese phosphate core by doping the elements A, B, C, and D into the Li site, manganese site, phosphorus site, and O site of lithium manganese phosphate, and then sequentially coating the surface of the core with three layers to provide a new type of core-shell structured cathode active material, which can greatly reduce the occurrence of Li / Mn antisite defects, significantly reduce the dissolution of manganese, reduce the lattice change rate, and increase the compaction density, and can be used in secondary batteries to improve the capacity of the secondary batteries, and improve the cycle performance, high-temperature storage performance, and safety performance of the secondary batteries.

[0135] In some embodiments, the step of providing a core material comprises: (1) mixing a source of manganese, a source of element B, an acid and a selective solvent to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, and a source of element D, and an optional solvent, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

[0136] In some embodiments, step (1) involves mixing at 60° C.-120° C. (e.g., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.) and / or mixing in step (1) involves stirring at a rotation speed of 200-800 rpm (e.g., 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm).

[0137] In some embodiments, mixing in step (2) is performed at a temperature of 20-120° C., optionally 40-120° C. (e.g., about 30° C., about 50° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.).

[0138] In some embodiments, in step (2), the mixing is carried out for 8-15 hours (eg, about 8 hours, about 9 hours, about 10 hours, about 11 hours, about 12 hours, about 13 hours, or about 14 hours).

[0139] When the temperature and time in the core particle manufacturing process are within the above ranges, the lattice defects in the manufactured core and the positive electrode active material manufactured thereby are relatively few, which is advantageous in suppressing the dissolution of manganese and reducing the interfacial side reaction between the positive electrode active material and the electrolyte, thereby improving the cycle performance and safety performance of the secondary battery.

[0140] In some embodiments, in step (2), the mixture is mixed under a condition of pH 3.5-6, optionally pH 4-6, more preferably pH 4-5. It should be noted that in the present application, the pH can be adjusted by a method commonly used in the art, such as by adding an acid or alkali.

[0141] In some optional embodiments, the mixture obtained in step (1) is filtered, dried and sand milled to obtain manganese salt particles doped with element B having a particle size of 50-200 nm, and the manganese salt particles doped with element B are used to mix with a lithium source, a phosphorus source, a source of element A, a source of element C and a source of element D and an optional solvent in step (2).

[0142] In some embodiments, optionally in step (2), the molar ratio of the mixture or manganese salt particles doped with element B to the lithium source and the phosphorus source is 1:0.4-2.1:0.1-2.1, optionally about 1:0.4-0.5:0.1-1.

[0143] In some embodiments, in step (2), sintering is performed at 600-900°C for 6-14 hours, and optionally sintering is performed at about 650°C, about 700°C, about 750°C, about 800°C, about 850°C, or about 900°C for about 2 hours, about 3 hours, about 4 hours, about 5 hours, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours. Optionally, sintering is performed in an inert gas or a mixed atmosphere of inert gas and hydrogen gas, and more preferably, the protective atmosphere is a mixed gas of 70-90% by volume of nitrogen gas and 10-30% by volume of hydrogen gas. Optionally, the sintering temperature and sintering time can be in any range of any of the above values, which can improve the crystallinity of the core, reduce the generation of heterophase, and maintain a certain particle size in the core, thereby improving the gram capacity and compaction density of the positive electrode active material, and improving the overall performance of the secondary battery, including the rate performance.

[0144] In some optional embodiments, step (2) involves drying in a spray drying facility.

[0145] In some optional embodiments, step (2) involves simultaneous mixing and grinding.

[0146] In some embodiments, in the first coating step, the first mixture is obtained by mixing a source of element M, a phosphorus source, an acid, and an optional lithium source with an optional solvent, and / or In a second coating step, a second mixture is obtained by mixing a source of element M′ with a solvent, and / or In a third coating step, a third mixture is obtained by mixing a carbon source with a solvent.

[0147] In some embodiments, in the first coating step, the source of element M, the phosphorus source, the acid, the optional lithium source, and the optional solvent are mixed at room temperature for 1-5 h (e.g., about 1.5 h, about 2 h, about 3 h, about 4 h, about 4.5 h, or about 5 h), then heated to 50° C.-120° C. (e.g., 55° C., about 60° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., or about 120° C.) and mixed at this temperature for 2-10 h (e.g., about 2 h, about 3 h, about 4 h, about 5 h, about 6 h, about 7 h, about 8 h, about 9 h, or about 10 h), all at a pH of 3.5-6.5 (e.g., 4-6).

[0148] In some embodiments, in the second coating step, the source of element M′ and the solvent are mixed at room temperature for 1-10 h (e.g., 1.5 h, about 2 h, about 3 h, about 4 h, about 4.5 h, about 5 h, about 6 h, about 7 h, about 8 h, about 9 h, or about 10 h) and then heated to 60° C.-150° C. (e.g., about 65° C., about 70° C., about 80° C., about 90° C., about 100° C., about 110° C., about 120° C., about 130° C., about 140° C., or about 150° C.) and maintained at this temperature for 2-10 h (e.g., about 2 h, about 3 h, about 4 h, about 5 h, about 6 h, about 7 h, about 8 h, about 9 h, or about 10 h).

[0149] The manufacturing method of the present application is not particularly limited with respect to the origin of the material, and the origin of a certain element may include one or more of the element's simple substance, sulfate, halide, nitrate, organic acid salt, oxide, and hydrogen oxide, provided that the origin can achieve the purpose of the manufacturing method of the present application.

[0150] In some embodiments, the source of element A is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate, and a sulfate of element A; and / or the source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The source of element D is one or more selected from a simple substance of element D and an ammonium salt thereof.

[0151] In some embodiments, the source of element M is one or more selected from the group consisting of an elemental salt, a carbonate, a sulfate, a halide, a nitrate, an organic acid salt, an oxide, and a hydrogen oxide of element M.

[0152] In some embodiments, the source of element M' is one or more selected from the element M' simple salt, carbonate, sulfate, halide, nitrate, organic acid salt, oxide and hydrogen oxide.

[0153] The amount of each of the sources of elements A, B, C, D, M, M' added depends on the target doping amount, and the ratio of the amounts of the lithium source, manganese source and phosphorus source used is in accordance with the stoichiometric ratio.

[0154] In the present application, the manganese source may be any manganese-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the manganese source may be one or more selected from elemental manganese, manganese dioxide, manganese phosphate, manganese oxalate, and manganese carbonate.

[0155] In the present application, the acid may be one or more selected from inorganic acids such as hydrochloric acid, sulfuric acid, nitric acid, phosphoric acid, silicic acid, metasilicic acid, and organic acids, for example, oxalic acid. In some embodiments, the acid is a dilute organic acid having a concentration of 60% by weight or less.

[0156] In the present application, the lithium source may be any lithium-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the lithium source may be one or more selected from lithium carbonate, lithium hydride, lithium phosphate, and lithium dihydrogen phosphate.

[0157] In the present application, the phosphorus source may be any phosphorus-containing material known in the art that can be used to prepare lithium manganese phosphate. By way of example, the phosphorus source may be one or more selected from diammonium hydrogen phosphate, ammonium dihydrogen phosphate, ammonium phosphate, and phosphoric acid.

[0158] In the present application, by way of example, the carbon source is one or more selected from starch, sucrose, glucose, polyvinyl alcohol, polyethylene glycol, citric acid.

[0159] In some embodiments, in the first coating step, sintering is performed at 650-800° C. (e.g., about 650° C., about 700° C., about 750° C., or about 800° C.) for 2-6 hours (about 2 hours, about 3 hours, about 4 hours, about 5 hours, or about 6 hours); and / or In the second coating step, sintering is performed at 500-700° C. (e.g., about 550° C., about 600° C., or about 700° C.) for 6-10 hours (e.g., about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours); and / or In the third coating step, sintering is performed at 700-800° C. (eg, about 700° C., about 750° C., or about 800° C.) for 6-10 hours (eg, about 6 hours, about 7 hours, about 8 hours, about 9 hours, or about 10 hours).

[0160] In the above first coating step, second coating step, and third coating step, drying is performed at a drying temperature of 100°C to 200°C, optionally 110°C to 190°C, more optionally 120°C to 180°C, even more optionally 120°C to 170°C, and most optionally 120°C to 160°C, and the drying time is 3-9 hours, optionally 4-8 hours, more optionally 5-7 hours, and most optionally about 6 hours.

[0161] [Positive electrode plate] The present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode film layer includes the positive electrode active material described above or the positive electrode active material manufactured by the manufacturing method described above, and optionally, the content of the positive electrode active material in the positive electrode film layer is 10 wt % or more, calculated based on the total weight of the positive electrode film layer.

[0162] In some embodiments, the content of the positive electrode active material in the positive electrode film layer is 90-99.5 wt %, calculated based on the total weight of the positive electrode film layer, to ensure that the secondary battery has a relatively high capacity and relatively good cycle performance, high temperature storage performance and safety performance.

[0163] In some embodiments, the positive electrode current collector may be a metal foil sheet or a composite current collector. For example, an aluminum foil may be used as the metal foil sheet. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer base layer. The composite current collector may be formed by forming a metal material (such as aluminum, aluminum alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0164] In some embodiments, the positive electrode film layer may further include other positive electrode active materials for batteries known in the art. For example, the positive electrode active material may include at least one material selected from the group consisting of lithium-containing phosphates with an olivine structure and modified compounds thereof. However, the present application is not limited to these materials, and other conventional materials that can be used as positive electrode active materials for batteries may also be used. These positive electrode active materials may be used alone or in combination of two or more. Here, examples of the lithium-containing phosphates with an olivine structure may include, but are not limited to, at least one of lithium iron phosphate (e.g., LiFePO4 (which may be abbreviated as LFP)), a composite material of lithium iron phosphate and carbon, lithium manganese phosphate (e.g., LiMnPO4), a composite material of lithium manganese phosphate and carbon, lithium manganese iron phosphate, and a composite material of lithium manganese iron phosphate and carbon.

[0165] In some embodiments, the positive electrode membrane layer more selectively includes an adhesive. For example, the adhesive may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.

[0166] In some embodiments, the positive electrode film layer more selectively includes a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, by way of example.

[0167] [Negative electrode plate] The negative electrode plate includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, the negative electrode film layer including a negative electrode active material.

[0168] For example, the negative electrode current collector has two opposing surfaces in the thickness direction of the negative electrode current collector, and the negative electrode film layer is disposed on either one or both of the two opposing surfaces of the negative electrode current collector.

[0169] In some embodiments, the negative electrode current collector may be a metal foil sheet or a composite current collector. For example, the metal foil sheet may be a copper foil. The composite current collector may include a polymer base layer and a metal layer formed on at least one surface of the polymer substrate. The composite current collector may be formed by forming a metal material (such as copper, copper alloys, nickel, nickel alloys, titanium, titanium alloys, silver, and silver alloys) on a polymer substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).

[0170] In some embodiments, the negative electrode active material may be a negative electrode active material for batteries known in the art. For example, the negative electrode active material may include at least one of artificial graphite, natural graphite, soft carbon, hard carbon, silicone-based materials, tin-based materials, and lithium titanate. The silicone-based material may be selected from at least one of silicone alone, silicone oxide, silicone carbon composite, silicone nitrogen composite, and silicone alloy. The tin-based material may be selected from at least one of tin alone, tin oxide, and tin alloy. However, the present application is not limited to these materials, and other conventional materials that can be used as a battery negative electrode active material may be used. These negative electrode active materials may be used alone or in combination of two or more.

[0171] In some embodiments, the negative electrode membrane layer more selectively includes an adhesive. For example, the adhesive may be selected from at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS).

[0172] In some embodiments, the negative electrode film layer more selectively includes a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers, for example.

[0173] In some embodiments, the negative electrode membrane layer optionally contains other auxiliary agents, such as a thickening agent (eg, sodium carboxymethylcellulose (CMC-Na)).

[0174] In some embodiments, the negative electrode plate can be manufactured in the following manner: Components for manufacturing the negative electrode plate, such as a negative electrode active material, a conductive agent, an adhesive, and any other components, are dispersed in a solvent (e.g., deionized water) to form a negative electrode slurry, which is then coated on a negative electrode current collector, and the negative electrode plate is obtained after processes such as drying and cold pressing.

[0175] [Electrolytes] The electrolyte serves to conduct ions between the positive and negative electrodes. The present application is not specifically limited to the type of electrolyte, which can be selected according to need. For example, the electrolyte may be liquid, gel, or all solid.

[0176] In some embodiments, the electrolyte is liquid and includes an electrolyte salt and a solvent.

[0177] In some embodiments, the electrolyte salt may be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonate), lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluoro(oxalato)borate, lithium bis(oxalato)borate, lithium difluorobis(oxalato)phosphate, and lithium tetrafluoro(oxalato)phosphate.

[0178] In some embodiments, the solvent may be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, sulfolane, dimethyl sulfone, ethyl methyl sulfone, and diethyl sulfone.

[0179] In some embodiments, the electrolyte may further include additives. For example, the additives may include anode film-forming additives, cathode film-forming additives, and may further include additives that can improve some performance of the battery, such as additives that improve the overcharge performance of the battery, additives that improve the high temperature or low temperature performance of the battery, etc.

[0180] [Separator] In some embodiments, the secondary battery further includes a separator. The present application is not particularly limited to the type of separator, and any known porous structure separator having good chemical stability and mechanical stability may be selected.

[0181] In some embodiments, the separator may be made of at least one of glass fiber, nonwoven fabric, polyethylene, polypropylene, and polyvinylidene fluoride. The separator may be a single layer film or a multi-layer composite film, without any particular limitation. When the separator is a multi-layer composite film, the materials of each layer may be the same or different, without any particular limitation.

[0182] In some embodiments, the positive plates, negative plates and separators can be fabricated into an electrode assembly by a winding process or a lamination process.

[0183] In some embodiments, the secondary battery may include an exterior body, which may be used to package the electrode assembly and the electrolyte.

[0184] In some embodiments, the exterior of the secondary battery may be a hard case, such as a hard plastic case, an aluminum case, a steel case, etc. The exterior of the secondary battery may be a pouch, such as a bag-shaped pouch. The material of the pouch may be plastic, such as polypropylene, polybutylene terephthalate, and polybutylene succinate.

[0185] The present application is not particularly limited to the shape of the secondary battery, which may be cylindrical, rectangular or any other shape. For example, FIG. 2 shows a secondary battery 5 having a rectangular structure as an example.

[0186] In some embodiments, referring to FIG. 3, the exterior body may include a case 51 and a cover plate 53. Here, the case 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate surround and form a receiving cavity. The case 51 has an opening communicating with the receiving cavity, and the cover plate 53 can cover the opening to seal the receiving cavity. The positive electrode plate, the negative electrode plate and the separator can form an electrode assembly 52 by a winding process or a stacking process. The electrode assembly 52 is packaged in the receiving cavity. The electrolyte is infiltrated into the electrode assembly 52. ​​The number of electrode assemblies 52 included in the secondary battery 5 may be one or more, and those skilled in the art can select it according to the actual needs.

[0187] In some embodiments, the secondary batteries may be assembled into a battery module, and the number of secondary batteries included in the battery module may be one or more, with the specific number being selectable by one skilled in the art depending on the application and capacity of the battery module.

[0188] Fig. 4 shows an example of a battery module 4. Referring to Fig. 4, in the battery module 4, the multiple secondary batteries 5 may be arranged in sequence along the longitudinal direction of the battery module 4. Of course, they may be arranged in any other manner. Furthermore, the multiple secondary batteries 5 may be fixed by fasteners.

[0189] Optionally, the battery module 4 may further include a housing having an accommodating space, and the multiple secondary batteries 5 are accommodated in the accommodating space.

[0190] In some embodiments, the battery modules may be further assembled into a battery pack, and the number of battery modules included in the battery pack may be one or more, and the specific number can be selected by one skilled in the art according to the application and capacity of the battery pack.

[0191] 5 and 6 show an example of a battery pack 1. Referring to Fig. 5 and Fig. 6, the battery pack 1 may include a battery box and a plurality of battery modules 4 installed in the battery box. The battery box includes an upper housing 2 and a lower housing 3, and the upper housing 2 may cover the lower housing 3 and form a sealed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.

[0192] The present application further provides a power consuming device, which includes at least one of the secondary battery, battery module, or battery pack according to the present application. The secondary battery, battery module, or battery pack may be used as a power source for the power consuming device, or may be used as an energy storage unit for the power consuming device. The power consuming device may include, but is not limited to, mobile devices (e.g., mobile phones, laptops, etc.), electric vehicles (e.g., pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.

[0193] As the power consuming device, a secondary battery, a battery module, or a battery pack can be selected according to the usage demand.

[0194] 7 shows an example of a power consumption device, such as a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. A battery pack or a battery module can be employed to meet the demand for high power and high energy density of the secondary battery of the power consumption device.

[0195] [Example] The following describes the examples of the present application. The examples described below are illustrative and are used only to interpret the present application, and should not be understood as limitations on the present application. If no specific techniques or conditions are specified in the examples, they are performed according to the techniques or conditions described in the literature in the field or according to the product specifications. If no manufacturer is specified, the reagents or equipment used are all ordinary products available on the market.

[0196] The origins of the raw materials used in the examples of this application are as follows: JPEG0007651064000001.jpg218150JPEG0007651064000002.jpg109150

[0197] Production of positive electrode active material and its slurry Example 1 Step S1: Preparation of doped manganese oxalate 1.3 mol of MnSO4·H2O and 0.7 mol of FeSO4·H2O are mixed thoroughly in a mixer for 6 hours, the mixture is transferred to a reaction vessel, 10 L of deionized water and 2 mol of oxalic acid dihydrate are added, heated to 80°C, and then stirred at a rotation speed of 600 rpm for 6 hours until the reaction is complete (no bubbles are generated), and a suspension of Fe-doped manganese oxalate is obtained. The suspension is filtered, the cake is dried at 120°C, and crushed to obtain a particle size of Dv 50 Fe-doped manganese oxalate particles of about 100 nm were obtained.

[0198] Step S2: Li 0.994 Mo 0.001 Mn 0.65 Fe 0.35 P 0.999 S 0.001 O 3.999 F 0.001 Manufacturing of cores including 1mol Fe-doped manganese oxalate particles, 0.497mol lithium carbonate, 0.001mol Mo(SO4)3, 0.999mol phosphoric acid containing 85% phosphoric acid aqueous solution, 0.001mol H4SiO4, 0.0005mol NH4HF2 and 0.005mol sucrose were added to 20L deionized water, the mixture was transferred to a sand mill machine and thoroughly ground and stirred for 10 hours to obtain a slurry, the slurry was transferred to a spray drying equipment for spray drying granulation, the drying temperature was set to 250℃, and dried for 4 hours to obtain particles, and the particles were sintered at 700℃ for 10 hours in a nitrogen gas (90%v / v) + hydrogen gas (10%v / v) protective atmosphere to obtain a core material. Inductively coupled plasma emission spectroscopy (ICP) was adopted to detect the element content of the core material, and the chemical formula of the core was obtained as above.

[0199] Step S3: Preparation of the suspension of the first coating layer Preparation of LiFeP0 solution: 7.4g lithium carbonate, 11.6g ferrous carbonate, 23.0g ammonium dihydrogen phosphate and 12.6g oxalic acid dihydrate were dissolved in 500mL deionized water, the pH was controlled at 5, and the solution was stirred and reacted at room temperature for 2h to obtain a solution, after which the solution was heated to 80°C and maintained at this temperature for 4h to obtain a suspension of the first coating layer.

[0200] Step S4: Coating the first coating layer 157.2 g of the doped lithium manganese phosphate core material obtained in step S2 was added to the suspension of the first coating layer obtained in step S3 (the coating material content is 1.572 g), stirred thoroughly and mixed for 6 h. After being mixed uniformly, it was transferred to an oven at 120°C for drying for 6 h, and sintered at 650°C for 6 h to obtain the material after being coated with pyrophosphate.

[0201] Step S5: Preparation of the suspension for the second coating layer 4.71 g of nano-Al2O3 (particle size is about 20 nm) was dissolved in 1500 mL of deionized water and stirred for 2 h to obtain a suspension of the second coating layer.

[0202] Step S6: Coating the second coating layer The 158.772 g pyrophosphate-coated material obtained in step S4 was added to the suspension of the second coating layer obtained in step S5 (the coating material content was 4.71 g), mixed thoroughly for 6 h, and after uniform mixing, transferred to an oven at 120°C for drying for 6 h, and then sintered at 700°C for 8 h to obtain a two-layer coated material.

[0203] Step S7: Preparation of the aqueous solution of the third coating layer 37.3 g of sucrose was dissolved in 500 g of deionized water, and stirred and thoroughly dissolved to obtain an aqueous sucrose solution.

[0204] Step S8: Coating the third coating layer 1633.9 g of the two-layer coated material obtained in step S6 was added to the sucrose solution obtained in step S7, and mixed together by stirring for 6 hours. After being mixed uniformly, it was transferred to an oven at 150°C for drying for 6 hours, and then sintered at 700°C for 10 hours to obtain a three-layer coated material.

[0205] Examples 2 to 89 and Comparative Examples 1 to 12 The positive electrode active materials of Examples 2 to 89 and Comparative Examples 1 to 12 were prepared in a manner similar to that of Example 1, and differences in the preparation of the positive electrode active materials are shown in Tables 1 to 6.

[0206] Here, Comparative Example 1-9 and Comparative Example 11 did not have steps S3-S4 since the first layer was not coated, and Comparative Example 1-10 did not have steps S5-S6 since the second layer was not coated.

[0207] [Table 1] JPEG0007651064000004.jpg234150JPEG0007651064000005.jpg234150JPEG0007651064000006.jpg234150JPEG0007651064000007.j pg234150JPEG0007651064000008.jpg234150JPEG0007651064000009.jpg234150JPEG0007651064000010.jpg234150JPEG00076510640 00011.jpg234150JPEG0007651064000012.jpg234150JPEG0007651064000013.jpg234150JPEG0007651064000014.jpg234150JPEG000 7651064000015.jpg234150JPEG0007651064000016.jpg234150JPEG0007651064000017.jpg234150JPEG0007651064000018.jpg236150

[0208]

Table 2

[0209]

Table 3

[0210]

Table 4

[0211]

Table 5

[0212] [Table 6] JPEG0007651064000035.jpg233150JPEG0007651064000036.jpg233150JPEG00076510640 00037.jpg233150JPEG0007651064000038.jpg233150JPEG0007651064000039.jpg236150

[0213] Positive electrode plate manufacturing The above-prepared triple-layered positive electrode active material, acetylene black as a conductive agent, and polyvinylidene fluoride (PVDF) as an adhesive were added to N-methylpyrrolidone (NMP) in a weight ratio of 97.0:1.2:1.8, and the mixture was stirred to obtain a positive electrode slurry. 2 The mixture was uniformly coated on an aluminum foil, dried, cold pressed and slit to obtain a positive electrode plate.

[0214] Negative electrode plate manufacturing The negative electrode active material, artificial graphite, the conductive agent, superconducting carbon black (Super-P), the adhesive, styrene butadiene rubber (SBR), and the thickener, sodium carboxymethyl cellulose (CMC-Na), were dissolved in deionized water in a mass ratio of 95%:1.5%:1.8%:1.7%, and thoroughly stirred to mix uniformly to obtain a negative electrode slurry with a viscosity of 3000 mPa.s and a solid content of 52%. The negative electrode slurry was coated on a negative electrode current collector copper foil of 6 μm, which was then baked at 100 °C for 4 hours, dried, and roll pressed to obtain a compaction density of 1.75 g / cm. 3A negative electrode plate was obtained.

[0215] Separator Polypropylene film was used.

[0216] Electrolyte production Ethylene carbonate, dimethyl carbonate and 1,2-propanediol carbonate were mixed in a volume ratio of 1:1:1, and LiPF6 was uniformly dissolved in the above solution to obtain an electrolyte solution, in which the concentration of LiPF6 was 1 mol / L.

[0217] Full battery production The positive electrode plate, separator, and negative electrode plate obtained above were stacked in order so that the separator was located between the positive and negative electrodes to play a role of isolation, and then wound to obtain a bare cell. The bare cell was placed in an exterior body, the electrolyte was injected, and the cell was packaged to obtain a full battery (hereinafter also referred to as a "full cell").

[0218] Button battery manufacturing The above positive electrode plate was assembled together with a negative electrode and an electrolyte into a button battery (hereinafter also referred to as a "button cell") in a button cell box.

[0219] I. Performance test of positive electrode active material 1. Lattice change rate test method: In a constant temperature environment of 25°C, the positive electrode active material sample was placed in an XRD (model number: Bruker D8 Discover), and the sample was tested at 1° / min. The test data was analyzed and sorted, and the lattice constants a0, b0, c0 and v0 (a0, b0 and c0 represent the length of each side of the unit lattice, and v0 represents the volume of the unit lattice, which can be obtained directly from the XRD finishing results) were calculated based on the standard PDF card.

[0220] The above-mentioned button cell manufacturing method was used to manufacture a positive active material sample into a button cell, and the button cell was charged at a low rate of 0.05C until the current was reduced to 0.01C. The positive electrode plate in the button cell was then taken out and placed in dimethyl carbonate (DMC) for 8 hours. It was then dried, the powder was scraped off, and particles with a particle size of less than 500nm were selected. The sample was then calculated to have a unit lattice volume v1 in the same manner as the above-mentioned fresh test sample, and (v0-v1) / v0×100% was defined as the lattice change rate (unit lattice volume change rate) before and after the lithium was completely released or absorbed.

[0221] 2. Measurement of Li / Mn antisite defect concentration: The XRD results tested using the "lattice change rate measurement method" were compared with the PDF (Powder Diffraction File) card of a standard crystal to obtain the Li / Mn antisite defect concentration. Specifically, the XRD results tested using the "lattice change rate measurement method" were introduced into the General Structure Analysis System (GSAS) software to automatically obtain the refinement results, which included the occupancy status of different atoms, and the Li / Mn antisite defect concentration was obtained by reading the refinement results.

[0222] 3. Measurement of compaction density: 5 g of the above-prepared positive electrode active material powder was taken and placed in a compaction mold (USA CARVER mold, model number 13 mm), and the mold was placed on a compaction density meter. A pressure of 3 T was applied, and the powder thickness at pressure (thickness after decompression) was read on the instrument, and the compaction density was calculated from ρ = m / v, where the area value used is the standard small image area of ​​1540.25 mm 2 It is.

[0223] 4. 3C charging constant current ratio measurement: In a constant temperature environment of 25°C, fresh full batteries manufactured in each of the above examples and comparative examples were left to stand for 5 minutes, and then discharged at 1 / 3C to 2.5V. After standing for 5 minutes, the batteries were charged at 1 / 3C to 4.3V, and then charged at a constant voltage of 4.3V until the current was 0.05mA or less. After standing for 5 minutes, the charge capacity at this time was recorded as C0. The batteries were discharged at 1 / 3C to 2.5V, left to stand for 5 minutes, and then charged at 3C to 4.3V, and then left to stand for 5 minutes. The charge capacity at this time was recorded as C1. The 3C charge constant current ratio was C1 / C0 x 100%.

[0224] It was explained that the higher the 3C charging constant current ratio, the better the rate performance of the secondary battery.

[0225] 5. Transition metal Mn (and Fe doped on Mn site) dissolution test: After cycling at 45° C. until the capacity was attenuated to 80%, the full batteries manufactured using the positive active materials of the above Examples and Comparative Examples were discharged at a rate of 0.1 C to a cut-off voltage of 2.0 V. The batteries were then disassembled, the negative electrode plate was taken out, and 30 unit areas (1540.25 mm2) were placed on the negative electrode plate. 2 ) wafers were randomly taken and tested for inductively coupled plasma emission spectrum (ICP) using an Agilent ICP-OES730. Based on the ICP results, the amount of Fe (when Fe is doped into the Mn site of the positive electrode active material) and Mn were calculated, and the amount of Mn (and Fe doped into the Mn site) eluted after cycling was calculated accordingly. The test standard was in accordance with EPA-6010D-2014.

[0226] 6. Measurement of surface oxygen valence states: A sample of 5 g of the prepared positive active material was taken and prepared into a button cell according to the method for preparing the button cell. The button cell was charged at a low rate of 0.05 C until the current was reduced to 0.01 C. The positive plate in the button cell was then taken out and placed in DMC for 8 hours for immersion. It was then dried, the powder was scraped off, and the particles with a particle size of less than 500 nm were selected. The particles obtained were measured by electron energy loss spectroscopy (EELS, the model number of the instrument used was Talos F200S) to obtain the energy loss near edge structure (ELNES), which reflected the state density and energy level distribution of the elements. From the state density and energy level distribution, the valence band state density data was integrated to calculate the number of occupied electrons, thereby estimating the valence state of the surface oxygen after charging.

[0227] 7. Measurement of manganese and phosphorus elements in positive electrode active material: 5g of the above prepared positive active material was dissolved in 100ml of reverse aqua regia (concentrated hydrochloric acid: concentrated nitric acid = 1:3) (concentrated hydrochloric acid concentration ~ 37%, concentrated nitric acid concentration ~ 65%), and the content of each element in the solution was tested using ICP, and the content of manganese element or phosphorus element was measured and converted (amount of manganese element or phosphorus element / amount of positive active material * 100%) to obtain their weight ratio.

[0228] 8. Method for measuring initial gram capacity of button battery: The button batteries prepared in the above Examples and Comparative Examples were charged at 0.1C to 4.3V at 2.5-4.3V, then charged at a constant voltage of 4.3V until the current was 0.05mA or less, left to stand for 5min, and discharged at 0.1C to 2.0V. The discharge capacity at this time was the initial gram capacity and was recorded as D0.

[0229] 9. Battery core expansion test with full battery stored at 60℃ for 30 days: The full batteries manufactured in the above examples and comparative examples were stored at 100% state of charge (SOC) at 60°C. The open circuit voltage (OCV) and alternating current internal resistance (IMP) of the battery core were measured to monitor the SOC before, during and after storage, and the volume of the battery core was measured. Here, after every 48 hours of storage, the full batteries were taken out and left to stand for 1 hour before testing the open circuit voltage (OCV) and internal resistance (IMP). After cooling to room temperature, the volume of the battery core was measured by the drainage method. In the drainage method, the gravity F1 of the battery core was measured independently using a balance that automatically converts units using the dial data, and then the battery core was completely immersed in deionized water (density 1 g / cm 3 The battery core is then placed in a vertical position (known as the gravity force F2) and the buoyancy force F acting on the battery core is measured. 浮 is F1-F2, and Archimedes principle

number

number

[0230] From the results of the OCV and IMP tests, the batteries of all the examples maintained an SOC of 99% or more throughout the entire test period until the end of storage.

[0231] After storage for 30 days, the volume of the battery core was measured, and the increase rate of the battery core volume after storage relative to the battery core volume before storage was calculated.

[0232] 10. Cycle performance test of full battery at 45℃: In a constant temperature environment of 45℃, charge at 2.5-4.3V at 1C to 4.3V, then charge at 4.3V with a constant voltage of ≦0.05mA, leave it for 5min, and discharge at 1C to 2.5V. The capacity is D n (n=0, 1, 2, ......) The above process was repeated until the capacity faded to 80%, and the number of repetitions was recorded, i.e., the number of cycles corresponding to 80% capacity retention at 45°C.

[0233] 11. Interplanar spacing and angle test: 1 g of each of the positive electrode active material powders prepared above was placed in a 50 mL test tube, and 10 mL of alcohol with a mass fraction of 75% was poured into the test tube, and the mixture was thoroughly stirred and dispersed for 30 minutes. Then, an appropriate amount of the above solution was taken using a clean disposable plastic straw and dropped onto a 300 mesh copper net. At this time, some of the powder remained on the copper net. The copper net was transferred together with the sample into a TEM (Talos F200s G2) sample cavity for testing, and the original image of the TEM test was obtained, and the original image format (xx.dm3) was saved.

[0234] The original image obtained in the above TEM test was opened in DigitalMicrograph software, and a Fourier transform was performed (the software completed automatically after a click) to obtain the diffraction pattern. The distance from the diffraction spot to the center position in the diffraction pattern was measured to obtain the lattice spacing, and the angle was calculated using the Bragg equation.

[0235] By comparing the obtained lattice spacing and corresponding angle data with their standard values, it was possible to distinguish the materials and crystallinity of the different coating layers.

[0236] 12. Coating thickness test: The thickness and size of the coating layer were examined by cutting a thin slice with a thickness of about 100 nm from the middle of a single particle of the positive electrode active material prepared above mainly by FIB, and then performing a TEM examination on the thin slice to obtain an original image of the TEM examination and preserve the original image format (xx.dm3).

[0237] The original image obtained in the above TEM test was opened with DigitalMicrograph software, and the coating layer was identified based on the angle information formed with the lattice pitch, and the thickness of the coating layer was measured.

[0238] For a selected particle, the thickness was measured at three locations and the average value was taken.

[0239] 13. Measurement of the molar ratio of SP2 to SP3 forms in the third overcoat carbon: This test was carried out by Raman spectroscopy. By performing peak division on the energy spectrum of the Raman test, Id / Ig was obtained, where Id is the peak intensity of SP3 carbon form and Ig is the peak intensity of SP2 carbon form, thereby confirming the molar ratio of both.

[0240] 14. Determination of the chemical formula of the core and the composition of the different coating layers: A spherical aberrometer (ACSTEM) was employed to characterize the internal microstructure and surface structure of the positive active material with high spatial resolution, and combined with three-dimensional reconstruction technology, the chemical formula of the core of the positive active material and the composition of different coating layers were obtained.

[0241] The performance test results of the positive electrode active materials of the examples and comparative examples are shown in the table below.

[0242] [Table 7] JPEG0007651064000043.jpg236150JPEG0007651064000044.jpg236150JPEG0007651064000045.jpg236150JPEG00076510640 00046.jpg236150JPEG0007651064000047.jpg236150JPEG0007651064000048.jpg236150JPEG0007651064000049.jpg236150 JPEG0007651064000050.jpg236150JPEG0007651064000051.jpg236150JPEG0007651064000052.jpg236150JPEG00076510640 00053.jpg236150JPEG0007651064000054.jpg236150JPEG0007651064000055.jpg236150JPEG0007651064000056.jpg236150

[0243] [Table 8] JPEG0007651064000058.jpg235150JPEG0007651064000059.jpg235150JPEG0007651064000060.jpg235150JPEG00076510640 00061.jpg235150JPEG0007651064000062.jpg235150JPEG0007651064000063.jpg235150JPEG0007651064000064.jpg237150

[0244] As can be seen from Tables 7-8, compared with the comparative examples, the examples achieved smaller lattice change rates, smaller Li / Mn antisite defect concentrations, larger compaction densities, surface oxygen valence states closer to -2, smaller amounts of Mn and Fe eluted after fewer cycles, and better battery performance, such as higher button cell capacity, better high-temperature storage performance, higher safety, and better cycle performance.

[0245] [Table 9] JPEG0007651064000066.jpg238150JPEG0007651064000067.jpg238150JPEG0007651064000068.jpg238150 JPEG0007651064000069.jpg238150JPEG0007651064000070.jpg238150JPEG0007651064000071.jpg238150

[0246] As can be seen from Table 9, the present application achieves smaller lattice change rate, smaller Li / Mn antisite defect concentration, larger compaction density, a surface oxygen valence state closer to -2, less Mn and Fe elution amount after fewer cycles, and better battery performance, such as higher button cell capacity, better high temperature storage performance, higher safety, and better cycle performance, by performing overall doping and triple coating on the Li, Mn, P and O sites of the lithium manganese iron phosphate.

[0247] [Table 10]

[0248] As can be seen from Table 10, with the increase in the crystallinity of pyrophosphate in the positive electrode active material, the compaction density gradually increases, the 3C charging constant current ratio increases, the amount of Mn and Fe dissolved after cycling decreases, the button cell capacity increases, and the high temperature storage performance, safety performance and cycle performance are all improved.

[0249] It should be noted that the present application is not limited to the above-mentioned embodiment. The above-mentioned embodiment is merely an example, and any embodiment having substantially the same configuration as the technical idea and achieving the same effect within the scope of the technical solution of the present application is included in the technical scope of the present application. In addition, various modifications that a person skilled in the art can make to the embodiment and other methods configured by combining some of the components in the embodiment are also included in the scope of the present application, within the scope of the purpose of the present application. [Explanation of symbols]

[0250] 1 battery pack, 2 upper housing, 3 lower housing, 4 battery module, 5 secondary battery, 51 case, 52 electrode assembly, 53 cover plate.

Claims

1. A positive electrode active material having a core-shell structure, comprising a core and a shell covering the core, The core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1, y is selected from any number in the range of 0.001-0.6, z is selected from any number in the range of 0.001-0.1, n is selected from any number in the range of 0.001-0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C is one or more elements selected from B, S, Si and N, and D is one or more elements selected from S, F, Cl and Br; The shell includes a first coating layer coating the core, a second coating layer coating the first coating layer, and a third coating layer coating the second coating layer, wherein: The first coating layer is made of crystalline Li pyrophosphate. a MP 2 O 7 And / or M b (P 2 O 7 ) c wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; and the crystalline Li pyrophosphate a MP 2 O 7 and M. b (P 2 O 7 ) c M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb, and Al; The second coating layer is an oxide M' d O e wherein d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, and M' is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides, and Sb; The third coating layer is a positive electrode active material containing carbon and having a core-shell structure.

2. the ratio of 1-y to y is 0.67-999; and / or 2. The positive electrode active material according to claim 1, wherein the ratio of m to x is 9 to 1100.

3. and / or, x is any number in the range of 0.001-0.005; and / or, y is any number in the range of 0.01-0.5; and / or and / or, z is any number in the range of 0.001-0.005; and / or 3. The positive electrode active material according to claim 1, wherein n is an arbitrary numerical value within a range of 0.001 to 0.

005.

4. 3. The positive electrode active material according to claim 1, wherein the carbon in the third coating layer is a mixture of SP2 carbon and SP3 carbon.

5. The coating amount of the first coating layer is greater than 0 and less than or equal to 6 wt. % based on the weight of the core, and / or The amount of the second coating layer is greater than 0 and less than or equal to 6% by weight based on the weight of the core, and / or 3 . The positive electrode active material according to claim 1 , wherein a coating amount of the third coating layer is greater than 0 and not greater than 6 wt % based on the weight of the core.

6. the thickness of the first coating layer is 1-10 nm; and / or the thickness of the second coating layer is 2-25 nm; and / or 3. The positive electrode active material according to claim 1, wherein the third coating layer has a thickness of 2 to 25 nm.

7. Based on the weight of the positive electrode active material, The content of elemental manganese is in the range of 10%-35% by weight, and / or 3. The positive electrode active material according to claim 1, wherein the content of phosphorus element is within the range of 12% by weight to 25% by weight.

8. The lattice spacing of the crystalline pyrophosphate in the first coating layer is in the range of 0.293-0.470 nm; and / or 3. The positive electrode active material according to claim 1, wherein the range of the angle made with the crystal direction (111) of the crystalline pyrophosphate in the first coating layer is 29.00° to 30.00°.

9. 3. The positive electrode active material according to claim 1, wherein a lattice change rate of the positive electrode active material before and after complete desorption or absorption of lithium is 8.1% or less.

10. 3. The positive electrode active material according to claim 1, wherein the positive electrode active material has a Li / Mn antisite defect concentration of 4% or less.

11. The compaction density of the positive electrode active material at 3t is 1.98 g / cm 3 The positive electrode active material according to claim 1 or 2.

12. 3. The positive electrode active material according to claim 1, wherein the valence state of surface oxygen of the positive electrode active material is −1.90 or less.

13. A method for producing a positive electrode active material, comprising: Providing a core material, the core material comprising Li m A x Mn 1-y B y P 1-z C z O 4-n D n wherein m is selected from any number in the range of 0.9-1.1, x is selected from any number in the range of 0.001-0.1, y is selected from any number in the range of 0.001-0.6, z is selected from any number in the range of 0.001-0.1, n is selected from any number in the range of 0.001-0.1, A is one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, B is one or more elements selected from Ti, V, Zr, Fe, Ni, Mg, Co, Ga, Sn, Sb, Nb and Ge, C is one or more elements selected from B, S, Si and N, and D is one or more elements selected from S, F, Cl and Br; Li pyrophosphate a MP 2 O 7 and / or M b (P 2 O 7 ) c a first coating step of mixing a core material with the first mixture, drying and sintering to obtain a material coated with a first coating layer, wherein a is greater than 0 and less than or equal to 2, b is any number within the range of 1-4, and c is any number within the range of 1-3; a MP 2 O 7 and M. b (P 2 O 7 ) c a first coating step, wherein M is independently one or more elements selected from Fe, Ni, Mg, Co, Cu, Zn, Ti, Ag, Zr, Nb and Al; Oxide M' d O e a second coating step of mixing a material to be coated with the first coating layer with the second mixture, drying and sintering to obtain a material to be coated with two coating layers, wherein d is greater than 0 and less than or equal to 2, e is greater than 0 and less than or equal to 5, and M' is one or more elements selected from alkali metals, alkaline earth metals, transition metals, Group IIIA elements, Group IVA elements, lanthanides, and Sb; providing a third mixture containing a carbon source, mixing a material to be coated with the two coating layers with the third mixture, drying and sintering the material to obtain a positive electrode active material; Here, the positive electrode active material has a core-shell structure, which includes the core and a shell covering the core, and the core is Li m A x Mn 1-y B y P 1-z C z O 4-n D n The shell includes a first coating layer that coats the core, a second coating layer that coats the first coating layer, and a third coating layer that coats the second coating layer, and the first coating layer is a crystalline Li pyrophosphate. a MP 2 O 7 And / or M b (P 2 O 7 ) c and the second coating layer comprises an oxide M' d O e wherein the third coating layer contains carbon.

14. The step of providing a core material comprises: (1) mixing a manganese source, a source of element B, and an acid to obtain a mixture; The mixture is mixed with a lithium source, a phosphorus source, a source of element A, a source of element C, and a source of element D, dried, sintered, and Li m A x Mn 1-y B y P 1-z C z O 4-n D n and (2) obtaining a core material comprising:

15. In the first coating step, the first mixture is obtained by mixing a source of element M, a phosphorus source, an acid, an optional lithium source with an optional solvent; and / or In said second coating step, a second mixture is obtained by mixing a source of element M′ with a solvent, and / or The method according to claim 13 or 14, wherein in the third coating step, the third mixture is obtained by mixing a carbon source with a solvent.

16. The source of element A is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element A; and / or The source of element B is one or more selected from the group consisting of an element, an oxide, a phosphate, an oxalate, a carbonate and a sulfate of element B; and / or the source of element C is one or more selected from sulfates, borates, nitrates and silicates of element C; and / or The method according to claim 13 or 14, wherein the source of the element D is one or more selected from an elemental substance of the element D and an ammonium salt thereof.

17. In the first coating step, the sintering is performed at 650-800° C. for 2-6 hours; and / or In the second coating step, the sintering is performed at 500-700° C. for 6-10 hours; and / or The method for producing a positive electrode active material according to claim 13 or 14, wherein in the third coating step, the sintering is carried out at 700-800° C. for 6-10 hours.

18. A positive electrode plate comprising a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector, the positive electrode film layer comprising the positive electrode active material according to claim 1 or 2.

19. A secondary battery comprising the positive electrode active material according to claim 1.

20. A battery module comprising the secondary battery according to claim 19.

21. A battery pack comprising the battery module of claim 20.

22. 22. A power consuming device comprising at least one selected from the group consisting of the secondary battery according to claim 19, the battery module according to claim 20, and the battery pack according to claim 21.

Citation Information

Patent Citations

  • Positive electrode material for lithium ion batteries, method for manufacturing the same and application thereof

    JP2016127002A

  • Manufacturing method of cathode active material composite material for lithium ion secondary battery

    JP2020113377A